PowerPoint, communication, and the knowledge society - Knoblauch, Hubert (Learning in doing, 2013)
"PowerPoint has become an integral part of academic and professional life across the globe. In this book, Hubert Knoblauch offers the first complete analysis of the PowerPoint presentation as a form of communication. Knoblauch charts the diffusion of PowerPoint and explores its significance as a ubiquitous and influential element of contemporary communication culture. His analysis considers the social and intellectual implications of the genre, focusing on the dynamic relationships between the aural, visual and physical dimensions of PowerPoint presentations, as well as the diverse institutional contexts in which these presentations take place. Ultimately, Knoblauch argues that the parameters of the PowerPoint genre frames the ways in which information is presented, validated and absorbed, with ambiguous consequences for the acquisition and transmission of knowledge. This original and timely book is relevant to scholars of communications, sociology and education" -- Provided by publisher.